Lokananta Arsip Sejarah Musik Indonesia yang Terlupakan - Gading Pramu Wijaya (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2019)
The title of this research is “The Analysis of Employees’ Performance in order to maintain Vinyl Archives Record in Music Record Company (Label) Lokananta”. How the archival system and vinyl record maintenance applied in Lokananta is becoming the issue of this research. The purpose of this research is to determine the employees’ performance in running and maintaining archival system applied in Lokananta along with a wide range of existing problems when archiving and maintaining the archives. This research is a qualitative descriptive research with the form of case studies in which the triangulation of data collection techniques can be found using observation and interview. The participants have been selectedbased on specific considerations (purposive sampling) and it consists of five participants. The findings revealed that Lokananta is a state-owned company that has a collection of various folk songs from Sabang to Merauke, state speech, and famous musicians of antiquity in the form of vinyl records. However, since 1972 the production of vinyl records stopped and Lokananta changed into a place to keep and maintain the archives of vinyl records. Archives system and disc maintenance applied in Lokananta still very simple, it had not met the standards archives system and maintenance applied by the National Archives of the Republic of Indonesia (ANRI) yet. The employees thought that the lack of human resources’ educational background Archives was one thing that hampersthem in archiving and maintaining records at Lokananta. Besides that, the lack of support facilities, infrastructure, and budgets of government is also the things that can hamper the activity. Since Lokananta separate with RRI and production of vinyl records dismissed, facilities, infrastructure, and budgets of government as well as dismissed.